Effectiveness of greater occipital nerve blocks in chronic migraine - Aciman Demirel, Esra; Karpuz, Burcu; Özdemir, Sibel; Kalaycı, Gülcan; Atasoy, Hüseyin Tuğrul (Journal of Surgery and Medicine, 2021)
Background/Aim: Chronic migraine (CM) is defined as headache occurring on 15 or more days per month for more than three months, which, on at least 8 days per month, has the features of a migraine headache. Greater occipital nerve (GON) blocks with local anesthetics and steroids are used in CM. GON block is widely used effectively in CM treatment. The aim of this study was to assess the effectiveness of GON blocks in CM. Methods: This retrospective cohort study was conducted in Bulent Ecevit University Faculty of Medicine, Department of Neurology. Data of 43 CM patients who had GON block were collected. CM was diagnosed using International Classification of Headache Disorders (ICHD-3). GON blocks were repeated every week in the first month and monthly thereafter for the following 6 months. The injections were performed radially at 2 cm lateral and 2 cm inferior to the protuberantia occipitalis externa with a needle and 2 mL of 0.25% bupivacaine bilaterally. Headache attack frequency (days), headache duration (hours) and severity of pain (Visual Analog Scale (VAS)) were compared between before and after GON block in the first month. Results: Headache attack frequency decreased from 12.8 (8.4) (pretreatment) to 3.8 (3.5), and headache severity (VAS), from 8.5 (1.2) to 4.5 (1.8) (P<0.001 for both) within one month. No serious adverse effects were observed. Conclusion: This study showed significant decreases in headache parameters in CM. GON block is widely used effectively in CM treatment, and there is a need to standardize the application technique, dose, and frequency.